SISTEM PENGENDALIAN INTERNAL, FRAUD DIAMOND, DAN LARCENY SEBAGAI EFEK MEDIASI WHISTLEBLOWINGSYSTEM (STUDI PADA BPK RI) - Krystella Krystella; Tigor Sitorus (Jurnal Akuntansi, 2017)
This research is aim to determine the effect of internal control system, fraud diamond, and whistleblowingsystem on larceny at BPK RI. Research data was obtained through questionnaires distributed torespondent, the employees in the work unit of General Bureau, IT Bureau, Human Resources Bureau and Leaders Secretariat Bureau BPK RI. So as many as 105 samples collected. This research used quantitative analysis technique with Structural Equation Modeling (SEM) processed with Amos 23. The test results showed : 1) Internal control system variable has positive and significant influence on whistleblowingsystem, 2) fraud diamond variable has not significant influence on whistleblowingsystem, 3) whistleblowingsystem variable has negative and significant influence on larceny, 4) internal control system variable has not significant influence on larceny, 5) fraud diamond variable has positive and significant influence on larceny. Therefore, the whistleblowingsystem mediation effect of the internal control system influence on larceny is perfectly significant. While the effect of fraud diamond on larceny is not proven to mediate.